The Dramatic Structure of Zemlinsky’s Eine florentinische Tragödie (Journal of Music Research Online, 2022)
This article discusses Zemlinsky’s opera Eine florentinische Tragödie, based on an unfinished play by Oscar Wilde. After the Introduction and a brief note on leitmotifs, the paper analyses the nine challenges that the fabric merchant, Simone, sets to Prince Guido Bardi. The emphasis is on how the text and music show the development of Simone’s thoughts and feelings. The cumulative results of the first eight challenges convince Simone that Guido is having an affair with his wife Bianca. He challenges Guido to a duel, wins it and kills him.Husband and wife are then reconciled. But this conclusion to the opera has been controversial since the first performances. The discussion concludes by evaluating two ways of improving on Wilde and Zemlinsky’s ending, both of which have been seen on stage in twenty-first century productions.